Anomalous metal vaporization from Pt/Pd/Al2O3 under redox conditions. Issue 26 (23rd June 2021) - Meng, Andrew C.; Low, Ke-Bin; Foucher, Alexandre C.; Li, Yuejin; Petrovic, Ivan; Stach, Eric A.
Abstract : Al2 O3 -supported Pt/Pd bimetallic catalysts were studied using in situ atmospheric pressure and ex situ transmission electron microscopy. Abstract : Al2 O3 -supported Pt/Pd bimetallic catalysts were studied using in situ atmospheric pressure and ex situ transmission electron microscopy. Real-time observation during separate oxidation and reduction processes provides nanometer-scale structural details – both morphology and chemistry – of supported Pt/Pd particles at intermediate states not observable through typical ex situ experiments. Significant metal vaporization was observed at temperatures above 600 °C, both in pure oxygen and in air. This behavior implies that material transport through the vapor during typical catalyst aging processes for oxidation can play a more significant role in catalyst structural evolution than previously thought. Concomitantly, Pd diffusion away from metallic nanoparticles on the surface of Al2 O3 can also contribute to the disappearance of metal particles. Electron micrographs from in situ oxidation experiments were mined for data, including particle number, size, and aspect ratio using machine learning image segmentation. Under oxidizing conditions, we observe not only a decrease in the number of metal particles but also a decrease in the surface area to volume ratio. Some of the metal that diffuses away from particles on the oxide support can be regenerated and reappears back on the catalyst support surface under reducing conditions. These observations provide insight on how rapid cycling between oxidative and reductive catalytic operating conditions affects catalyst structure.